A novel biocompatible PDA/IR820/DAP coating for antibiotic/photodynamic/photothermal triple therapy to inhibit and eliminate Staphylococcus aureus biofilm - Zeng, Junkai; Wang, Yitong; Sun, Zhenyu; Chang, Haishuang; Cao, Mi; Zhao, Jie; Lin, Kaili; Xie, Youzhuan (Chemical engineering journal (Lausanne, Switzerland : 1996), 2020)
[Display omitted] •Easy-to-perform and cost-effective fabrication of PDA-IR820-DAP coating.•Triple therapy for Staphylococcus aureus biofilm.•Outstanding antibacterial and osseointegration-promoting performances. Surgical site infection (SSI) with instrumentation is an undesired and troublesome complication in orthopaedics. Surgical debridement is currently the main treatment option. However, the poor prognosis remains the major problem and over 40% of patients needed additional surgery to remove the implant. To eliminate SSI, antibacterial and biocompatible implants are urgently needed. Herein, a novel biocompatible polydopamine (PDA)-IR820-Daptomycin (DAP) coating with triple therapy functions was successfully fabricated to enhance the anti-infection ability and osteogenic property of titanium implants. In which, PDA served as a biocompatible binder to immobilize IR820 and DAP, and possessed photothermal and osteogenic properties. The releasing of DAP inhibited the growth of Staphylococcus aureus and damaged the bacterial membrane. Meanwhile, after 808 nm laser irradiation, the combination of hyperthermia generated by PDA and singlet oxygen (1O2) produced by IR820 eradicated the biofilm noninvasively. Furthermore, this coating successfully accelerated glutathione (GSH) oxidation and destroyed the bacterial membrane, reaching an anti-bacterial efficiency of 97.2% in vitro. Additionally, the coating significantly stimulated the proliferation and osteogenic differentiation of rat bone marrow stem cells (rBMSCs). In vivo, Ti-PDA-IR820-DAP reached an anti-bacterial efficiency of 97.9% in a S. aureus biofilm-infected rat model with 15 min of irradiation at 50 °C and drastically promoted the bone-implant osseointegration in a rat femur condyle defect model. The present study demonstrates that combining antibiotics and phototherapy represents a feasible way to treat bone-implant-associated infections.